Clara, Mônica e Joana: mulheres professoras em seus diferentes arranjos familiares - Nunes, William (2017)
In this study I aimed to understand the ways in which women teachers with different family arrangements, especially considering the presence and/or absence of the maternity and conjugality, experience the status of woman worker. The study was developed between the years of 2015 and 2017, as an ethnography on the universes of three woman teachers of the public-state education from Rio Grande do Sul who work in schools in the city of Acampamento, in the center of the state. They are: Clara, a married teacher with no children; Monica, a widow teacher with one daughter; and Joana, a teacher with a partner and two children. As a way of exploring the universes of each one of the teachers, the field work was done mainly from participant observation and from open and semi-structured interviews with the teachers. I also looked at the teacher’s informations and interactions on social networks, such as Facebook. The stories and experiences of each of them, within their singularities, demonstrated how much access to the teaching profession and the exercise of the teaching profession are still due to different constraints that relate to the possibilities and limits placed on the woman worker, from the forms that the sexual division of labor assumes in each epoch. Alongside this, it can be observed that the devaluation and the lack of recognition of the teaching profession appear not only as phenomem linked to neglect of public education, but also to the low value attributed to women's work, which, in turn, exposes the professional category to a process of degradation due to unsatisfactory conditions for the performance of its activities, generating disinterest and even producing the abandonment of the profession. The arrangements of the studied teacher’s families vary, they present themselves as different forms of organization that while deny the modern family model, they also are influenced by this model as a hegemonic social ideal. Therefore, those arrangements can only be understood as produced in a relation between the model of modern family and the particular social context that resignify them. The presence and/or absence of the maternity and conjugality are experienced by the teachers in different ways, but, in general, it was possible to perceive that those elements impose themselves as conditioning factors to the teachers experiences of working women, not naturally, but socially, since the creation of children and cohabitation with a partner still carry with them a series of assignments related to the home and family that are understood culturally as fundamentally feminine obligations, demanding from the teachers different articulations depending on the composition of their family arrangements.